Position and flux stabilization of X‐ray beams produced by double‐crystal monochromators for EXAFS scans at the titanium K‐edge. (31st January 2014) - van Silfhout, Roelof; Kachatkou, Anton; Groppo, Elena; Lamberti, Carlo; Bras, Wim
<x xml:space="preserve">Abstract</x> The simultaneous and active feedback stabilization of X‐ray beam position and monochromatic beam flux during EXAFS scans at the titanium K‐edge as produced by a double‐crystal monochromator beamline is reported. The feedback is generated using two independent feedback loops using separate beam flux and position measurements. The flux is stabilized using a fast extremum‐searching algorithm that is insensitive to changes in the synchrotron ring current and energy‐dependent monochromator output. Corrections of beam height are made using an innovative transmissive beam position monitor instrument. The efficacy of the feedback stabilization method is demonstrated by comparing the measurements of EXAFS spectra on inhomogeneous diluted Ti‐containing samples with and without feedback applied.